Meningkatkan Kreatifitas dan Inovatif dalam lintasan pembelajaran hipotetis pendidikan Islam pada era industri 4.0 - Muthoharun Afif (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Education, a major agenda of life requires trajectories in a continuous series of creativity and innovation, so that it is ordered to be sought from cradle to grave, or in other words lifelong education. In reaching an education there needs to be trajectories and not just transmitting knowledge. Islamic education must be returned to its essence, which is to prepare, direct, and return the goals of education to its essence. The core purpose of education is to make students understand and realize their position in the order of existence and creation of an orderly cosmos, and their relationship as creatures with Allah (khaliq). The purpose of this paper is to examine how to Increase Creativity and Innovation in the hypothetical learning trajectory of Islamic education in the industrial era 4.0. From the results of the discussion it was concluded: 1) Islamic education in the industrial revolution era 4.0 must be handled by Human Resources who truly become agents of transdisciplinary change. 2) The complete hypothetical learning trajectory covers all three aspects: learning objectives, thought development and learning, and the influence of instructional assignments. 3) efforts to